Incidence trend and disease burden of seven vaccine-preventable diseases in Shandong province, China, 2013–2017: Findings from a population-based observational study. (April 2022) - Li, Zhen-Wei; Yin, Chao-Nan; Wang, Hai-Tao; Du, Wan-Yu; Wang, Wen-Jing; Xue, Fu-Zhong; Zhao, Lin; Cao, Wu-Chun; ,
Abstract: Introduction: Although vaccines provide a cost-effective solution to vaccine-preventable diseases (VPDs), the disease burden of VPDs is still very high in most parts of the world. Methods: A population-based observational study was conducted in Shandong province, China, from 2013 to 2017, giving an insight into the epidemiological characteristics and disease burden of seven VPDs. The incidence trend was estimated using the Poisson regression model. The disease burden was calculated using the disability-adjusted life years (DALYs). Results: Most VPDs included in the China's National Immunization Program had higher incidence density (ID) in inland cities. The ID of mumps decreased significantly, while herpes zoster increased (both P < 0.05 ). The top three causes of the disease burden as assessed with DALYs included tuberculosis, herpes zoster, and hepatitis B, with the rates of 72.21, 59.99, and 52.10 DALYs/100 000, respectively. The disease burden of influenza and herpes zoster were relatively high in people aged > 50 years, while highest DALYs of hepatitis B were found in young adults. Conclusion: Inequalities in the vaccine coverage by geography, socio-economic status, and targeted population contribute to the increasing incidence and high burden of VPDs and call for renewed and sustained immunization strategies in China.